Intellectual property rights and plant genetic resources: Options for a Sui Generis system - Leskien, D.; Flitner, M.; International Plant Genetic Resources Institute (1997)
This study aims at the development and evaluation of elements for inclusion in an intellectual property rights system sui generis for the protection of plant varieties. Pursuant to the TRIPS Agreement, members shall provide patent protection for any inventions, whether products or processes, in all fields of technology. Members are allowed to exclude from patentability inter alia plants and animals other than micro-organisms. However, the TRIPS Agreement explicitly requires members to provide for the protection of plant varieties either ”by patents or by an effective sui generis system or by any combination thereof.” The report studies the legal obligations posed by the TRIPS Agreement in relation to plant genetic resources. It further analyzes the status of plant genetic resources under the existing international regulatory framework, in particular the Convention on Biological Diversity. The Study gives an overview of and discusses possible elements, for example recognition of Farmers' Rights, which, if included in a protection system for plant varieties, may contribute to reconciliation of the interests of formal breeders with the rights and interests of informal breeders. The study also examines the options for regulating the interface between a sui generis legislation and other intellectual property rights, such as patents. There is a broad range of possible TRIPS-compatibles sui generis systems. Those systems should be explored and discussed before ready-made protection system currently being used in many industrialized countries are adopted.